Temperature and Pressure Insensitive Spectroscopic Method for Measuring 13CH4 during Oil and Natural Gas Drilling Operations - Li, Guolin; Jiang, Qingzhi; Hua, Chenquan; Ma, Kun; Jiao, Yue; Ji, Wenhai (Frontiers in Physics, 2021)
A novel rugged two-section driving NIR TDLAS scheme was implemented to reduce temperature and pressure sensitivity of methane carbon isotope measurement during oil and natural gas drilling operations. Isotope spectra line groups with same lower energy levels were selected to derive the concentration of 13CH4 and 12CH4. Dynamic pressure linewidth broadening was introduced in the absorbance curve fitting. Various uncontrollable factors such as spectra shift, stretching, and baseline trending were incorporated in the comprehensive multi-peak fitting. The results showed that the sensitivity of isotope ratios to temperature and pressure variation was greatly suppressed. The δ13CH4 uncertainty in the temperature test was 2.8‰ with fitted δ13CH4-T slope of 0.021‰/℃ in 25±5℃ range. The δ13CH4 uncertainty in the pressure test was 1.4‰ with fitted δ13CH4-P slope of < 0.001‰/mbar from 400 to 1000 mbar. The limit standard deviation of long-term test was 0.15‰ (@135 s). The results indicate that our scheme is a promising solution for δ13CH4 measurement during drilling operations due to the enhanced robustness.